Halal Logistics through Value Co-Creation - iwan sukarno; Ananda P. Dermawan; Rahesya P. Syailendra; Intan R. Silalahi; Christ M. Purba; Juan S. Y. Simanjuntak (Jurnal Teknologika, 2022)
Increasing the number of consumers' awareness of halal products makes Dicaffe Dimsum & Coffee want to encourage the current condition of logistics activities to increase the guarantee of halal products. Therefore, it is necessary to create value for current conditions which are based on the principles of halal logistics in all business activities. The purpose of this research is to create Halal Logistics Value Co-Creation in order to provide maximum service on the basis of halal and tayyib principles for all products sold at Dicaffe Dimsum & Coffee. The data used are primary data, namely the results of interviews, and secondary data, namely historical data in the form of sales data and material supplier data. The results showed that the critical points are found in 4 activities: Receiving Product, Put Away, Storage, and Customer Service/Product. The increase in activities based on halal principles is based on 5 parameters including social factors, the proportion of product value, value creation, value delivery, and value capture